2016
DOI: 10.3329/bjp.v11i4.27517
|View full text |Cite
|
Sign up to set email alerts
|

Caryophyllene oxide exhibits anti-cancer effects in MG-63 human osteosarcoma cells via the inhibition of cell migration, generation of reactive oxygen species and induction of apoptosis

Abstract: <p class="Abstract">The main objective of the present study was to evaluate the antitumor and apoptotic effects of caryophyllene oxide in MG-63 human osteosarcoma cells. Cell viability of these cells was evaluated by MTT assay while as in vitro wound healing assay was used to study the effect of caryophyllene oxide on cell migration. Fluorescence microscopy and transmission electron microscopy were used to study the changes in cell morphology once the cells undergo apoptosis. Caryophyllene oxide signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…The other compound, eicosanoic acid, methyl ester, the second highest content of both extracts showed α-glucosidase inhibitor activity (Artanti et al, 2012). Caryophyllene oxide, a bicyclic sesquiterpene, showed strong anti-cancer effects against MG-63 human osteosarcoma cells through suppression of cancer cell migration tendency and induction of apoptosis (Pan et al, 2016). Furthermore, 9,12-octadecadienoic acid (Z,Z)-, methyl ester or methyl linoleate used as a flavouring ingredient possesses antifungal and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The other compound, eicosanoic acid, methyl ester, the second highest content of both extracts showed α-glucosidase inhibitor activity (Artanti et al, 2012). Caryophyllene oxide, a bicyclic sesquiterpene, showed strong anti-cancer effects against MG-63 human osteosarcoma cells through suppression of cancer cell migration tendency and induction of apoptosis (Pan et al, 2016). Furthermore, 9,12-octadecadienoic acid (Z,Z)-, methyl ester or methyl linoleate used as a flavouring ingredient possesses antifungal and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then treated with 10, 25 and 50 μg/mL μg/mL of plant based gold nanoparticles for 24 h. Culture medium was aspirated from each well and cells were gently rinsed twice with PBS, fixed with methanol: acetic acid for 10 min, and stained with 50 μg/ml Propidium iodide for 20 min. Nuclear morphology of apoptotic cells with condensed/fragmented nuclei was examined by fluorescence microscopy and at least 1 × 10 3 cells were counted for assessing apoptotic cell death [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relative abundance of each band was quantified using Image J software (version 1.43, NIH, USA) for Windows. Blots were reported with β- actin antibody as a loading control [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…At 20, 80,120µM concentrations, the cell migration was found to be 94.2, 67.1 and 14.8%. IC 50 values was found to be 43.2, 31.6 and 24.2µM at 24, 48, and 72 h. This concluded that cytotoxicity increases with increase in incubation time 25 . Wahid chaouki, David Y leger et al, studied potential activity on breast cancer (Mcf-7) by using four different extracts of Aristolochia baectica and Origanum compactum.…”
Section: Cytotoxic Study Of the Extract Was Initially Carried Out On Normal Cell Line (F929 Fibroblast Cells) And On Cancerous Cell Line mentioning
confidence: 74%